Revolutionary ideology and political destiny in Mexico, 1928-1934 : Lázaro Cárdenas and Adalberto Tejeda - Ginzberg, Eytan (Sussex Academic e-Library, 2015)
Lázaro Cárdenas and Adalberto Tejeda, veterans of the Revolution and prominent governors of Michoacán and Veracruz from 1928 to 1932, strived to make Mexico a modern and just state on the basis of the revolutionary Constitution. Three key obstacles confronted them: the conservative approach of the political Center; the political weakness of their own power base; and the great opposing power of the farmers and their supporting elements, especially the Church and the army. This book discusses the different avenues to reform these leaders took and their short- and long-term implications. Cárdenas sought to strengthen his position through the ruling party (PNR), while reinforcing local agrarian forces and opening channels of direct empathetic communication with the Church and the army. Tejeda attempted to strengthen his position in the federative arena, bypassing the political Center via the National Peasant League (LNC - Liga Nacional Campesina), whose establishment he was deeply involved in, making a sweeping radical reform while attacking uncompromisingly all the traditional elements of Veracruzan society. Both political projects had unprecedented success but totally different implications. The Cardenista power base led its author to the next Presidency, during which he implemented a remarkable agrarian project. Tejeda's power base, however, led to the utter annihilation of his political power structure and many of his agrarian achievements, as well as to his failure in the struggle for presidency.